Structural Change in Fiscal Policy and The Permanence of Fiscal Contractions - The Case of Denmark and Ireland - Göran Hjelm; Martin W Johansson (Lund University, School of Economics and Management, Department of Economics, 2002)
Instead of relying on descriptive statistics to evaluate the permanence of a fiscal contraction, this paper suggests that this issue should be studied using tests for structural breaks in cointegrating relationships between taxes and spending. We label a fiscal contraction as 'permanent' if a structural break is detected during the contraction period. Applying Gregory and Hansen's (1996) test on Danish and Irish data and find that the fiscal contraction in Ireland (1987-1989) induced a structural change in fiscal policy while the results from the Danish data do not imply such a regime shift. We discuss possible explanations for this finding
Keywords: C22; E62; H30; 330; Fiscal Policy; Fiscal contraction; Cointegration; Structural breaks